Phytochemical screening and antimicrobial activity of four members of family Apiaceae - Kaushal Sood; R NS Yadav (International Journal of Phytomedicine, 2014)
The aqueous extract of the four members- Hydrocotyle javanica Thunb., Hydrocotyle rotundifolia Roxb., Eryngium foetidum L. and Centella asiatica L.; of the family Apiaceae were screened for the phytochemicals and for antimicrobial activity against standard microbial strains by in vitro antimicrobial assay using agar well diffusion method. Phenolics, flavonoids and tannins were tested positive in all the four plant extracts. H. javanica emerged to be an effective inhibitor of five of the eight tested microbial strains. B. subtilis exhibited resistance to all the four plants. H. rotundifolia inhibited two strains which were less susceptible to the other plants. The study showed that these traditionally used herbs can be a useful source of antimicrobial agents and their use in the traditional system is scientifically justified.